ORIGIN AND ENVIRONMENTAL SIGNIFICANCE OF LARGE-SCALE PATTERNED GROUND, DONNELLY DOME AREA, ALASKA. - Church, Richard E.; Pewe, Troy L.; Andresen, Marvin J. (1965)
Large-scale patterned ground in the Donnelly Dome area of central Alaska consists of polygons 25 to 46 m in diameter bounded by shallow troughs 1 to 2 m wide that form the sides of the polygons. The troughs are underlain by wedge-shaped masses of sediments that extend downward 2 to 3 m. Texture of the sediments of the wedges is distinct from that of the poorly stratified glacial outwash gravel that the wedges transect. Sediments of the wedge vary texturally along the strike and vertically within a given wedge. The coarsest material in the wedge is about 75 mm in diameter, which is the same size as the coarsest material in the outwash. The fine material in the wedges is silt, the same as that which blankets the area. The patterned ground of the Donnelly Dome area originated during Wisconsin time when the mean annual air temperature was at least 3C colder than now. Wigh the warming of the climate in post-Wisconsin time most of the perennially frozen gravel thawed and the ice wedges melted. The voids created by the melting of the ice wedges were filled with sediment that was washed from the surface or collapsed from the thawed sides of the voids. The troughs bounding the polygons are now, however, no longer underlain with ice wedges but with ice wedge pseudomorphs (fossil ice wedges). (Author)